Analisis Kekuatan Tarik Komposit Hybrid Berpenguat Chip Daun Gewang Dan Serat Pendek E-Glass - Jefri S. Bale; Yeremias M. Pell; Kristomus Boimau; Finsensius Lelu (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2020)
The use of natural fiber as reinforcement for composite materials provides several advantages such as low density, biodegradable, easily recycled, inexpensive, good mechanical properties, and renewable because it comes from nature. One of the natural fibers that can be used as reinforcement for polymer composites is gewang leaves. This study aims to analyze the tensile strength of a hybrid composite with gewang leaf chip and E-glass short fiber reinforcement. The tensile strength of 61.25 Mpa and the stiffness modulus of 90.83 MPa produced by the E-glass fiber composite which is higher compared to the gewang leaf chip composite and the hybrid composite. The results showed that gewang leaf chip composite and the hybrid (gewang leaf chip + e-glass short fiber) can only be used for accessories applications such as car dashboards in the transportation industry that mechanical strength is not the prime factor.